SOSIALISASI GERAKAN PENGEMBANGAN KAWASAN AGROPOLITAN PROGRAM TO THE FARMER - Yanuarti Hapsari; Arip Wijianto; Sutarto Sutarto (AGRITEXTS: Journal of Agricultural Extension, 2016)
The aimed of this research is to know how the socialization Gerakan Pengembangan Kawasan Agropolitan (GPKA) Program, knowing constraint delayed on socialization   Movement Development Program of Agropolitan Dictrict (SMAD), and knowing the way of socialization  Gerakan Pengembangan Kawasan Agropolitan (GPKA) Program Regency of Boyolali. The method are used is kualitative with descriptive approach. Location of this research used purposive ways that on Regency of Boyolali. From Regency of Boyolali was choosen two subdistrict, that is subdistrict of Ampel and Boyolali. The informan are used with purposive ways and snowball sampling. The sources data its come from the informan, place and activities and also document/archieve. Whereas the technique to collected data had done with interview, observation, and content analysis. To measure of data used triangulation data (sources). The data was analysed by using reduction data, saw data, and verification.The result of this research showing that The Sosialization Gerakan Pengembangan Kawasan Agropolitan (GPKA) Program had done with elucidation/companionship with group farmer/GAPOKTAN, PPL, and official related, training, and contiguous. Constraint that fight are amount personil in concerned stint, presence either one staf section Agribisnis mutation, the farmer not all known about the GPKA program, cost limit for activity GPKA program, the farmer activity, and the farmer whole lot have same view and attitude about GPKA. The way used are coordinating amount personil in concerned, giving suggestion to tow removal the staf involved, the change information with farmer other, make proposal for GPKA Program, and coordination across sector intensived and contiguous.